Accessing participatory research impact and legacy: developing the evidence base for participatory approaches in health research. Issue 4 (8th August 2017) - Cook, Tina; Boote, Jonathan; Buckley, Nicola; Vougioukalou, Sofia; Wright, Michael
Abstract: Action research has been characterised as systematic enquiry into practice, undertaken by those involved, with the aim changing and improving that practice: an approach designed to have impact. Whilst much has been written about the process and practice of 'researching', historically 'impact' has been somewhat taken for granted. In recent years, however, the impact of all forms of research has become the focus of interest with many funding bodies now demanding that researchers not only articulate the prospective impact of their work, but what kinds of evidence will be proffered to demonstrate that impact. This has raised questions for action researchers, not about whether their work has an impact, but what form that impact takes, how it is recognised and by whom. This paper focuses on difficulties researchers find in both articulating the impact of participatory research and demonstrating links between such forms of research and impact. We draw on discussions about the notion of impact with authors that have self-reported and published their work as participatory. These discussions revealed that not only were there difficulties in clarifying the participatory dimension of their research but that whilst authors were able to discuss particular impacts of their work, articulating and evidencing that impact was often absent from their published papers. This paper offers insights into some of issues and barriers those who undertake participatory research face in explicating, for the external audience (and indeed sometimes for ourselves), the impact of this action-based form of enquiry.